STUDI OBSERVASIONAL TENTANG HAKIKAT IPAS DALAM PRAKTIK PEMBELAJARAN IPAS DI SEKOLAH DASAR: Studi pada siswa Kelas III Sd Negeri 04 Dondong - Athi Hamda Haniifa; Kurnia Rani Ardiningrum; Liyuhda Akmaludin Fakhri; Auralya Lintang Azlani; Sarla Kinanti Ayuningtyas; Uzlati Hasbiya Novaria; Aris Naeni Dwiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explain how Integrated Natural and Social Sciences (IPAS) is implemented in the elementary school curriculum. IPAS consists of three main components: product, process, and scientific attitude. A qualitative observational approach was employed in this study. Data were collected through direct observation of the IPAS learning process in the classroom, supported by field notes and documentation. Based on the research findings, IPAS learning in elementary schools has not yet reflected the three essential components of IPAS in a balanced manner. The delivery of learning materials by teachers indicates a greater emphasis on the product aspect. On the other hand, the process and scientific attitude aspects have not been optimally developed due to the lack of experiments, discussions, and activities aimed at fostering students’ curiosity. Therefore, it can be concluded that improving the quality of IPAS learning is necessary by placing greater emphasis on students’ active involvement in scientific processes and the development of scientific attitudes. Consequently, IPAS learning is expected to become more meaningful and contribute to the improvement of students’ overall competencies.